Youth Employment Transitions in Latin America - Cunningham, Wendy; Salvagno, Javier Bustos (2012)
Using panel data from labor force surveys in Argentina, Brazil, and Mexico, the paper maps out young people's paths from the classroom to the work place during the 1980s through the early 2000s. By decomposing transition matrices into propensity to move and rate of separation and estimating duration matrices, the authors follow young people's movements between school and work and between employment sectors to better understand the dynamics of youth employment, including where youth go upon leaving school, how long they spend in each state, and where they go upon leaving various employment states. The main conclusion of the study is that young people across all three countries follow a similar trend over their life cycle: they leave school to spend a short time in the informal sector, move to a formal position for longer spells, and finally become self-employed. The authors find evidence of decreasing segmentation between formal and informal sectors as workers age, a lower propensity for formal sector employees to return to school than workers in the same age cohort who are not in the formal sector, and that entry to self-employment is not subject to income constraints.